„Бог не уместится в книжке“ Orthodoxie, Islam und Tolstojs Poetik der Verfremdung - Jurij Murašov (Slavica TerGestina, 2013)
The first part of the article is about Tolstoy‘s idea of religion and the estimated role of the Islam in Tolstoy‘s religious thinking. Referring to the media theory of writing we start with some preliminary considerations about the interrelationship between aesthetic and religious communication. That way we try to understand the significant shift from aesthethic writing towards pedagogical and religious interests which can be traced within the evolutions of the „classical“ Russian writers of the 19th century like Nicolai Gogol, Fyodor Dostoevsky or Lev Tolstoy. In the case of Tolstoy Victor Shklovsky‘s poetics of estrangement gives us the possibility to analyse not only Tolstoy‘s novels but also his turn towards ethics and religion and to define the specifics of his religious discourse, where the poetics of estrangement continue to work. Crucial for Tolstoy‘s idea of religion is an obsessive rejection of book and literacy based forms of transcendent experience thus eliminating confessional differences. In this context we also find Tolstoy‘s remarkable estimation of the Islam.